Optimizing The Role Of Babinkamtibmas In Participatory Supervision Of Village Funds: A Community Policing Based Corruption Prevention Strategy To Accelerate Village Development - Eko Sujarwo (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
The Village Fund allocated by the central government to villages throughout Indonesia is a strategic instrument for accelerating development and improving the welfare of village communities. However, the implementation of this program is still colored by various corruption problems and irregularities that hinder the effectiveness of village development. The Bintara Pembina Pembina Seguridad and Public Order (Babinkamtibmas) as the spearhead of the National Police at the village level has a strategic position in participatory supervision of village funds through the community policing approach. This study aims to analyze the optimization of the role of Babinkamtibmas in participatory supervision of village funds as a community policing based corruption prevention strategy to accelerate village development. The research uses a normative juridical method with a statutory approach, a case approach, and a conceptual approach. The results of the study show that Babinkamtibmas has the authority and strategic position in supervising village funds through preemptive, preventive, and repressive functions. However, the optimization of this role is still constrained by limited technical regulations, human resource capacity, inter-agency coordination, and community participation. The optimization strategies needed include strengthening the legal foundation, increasing the capacity of Babinkamtibmas human resources, developing an integrated coordination system, and empowering the community through community policing. In conclusion, optimizing the role of Babinkamtibmas in participatory supervision of village funds requires synergy between strengthening regulations, increasing institutional capacity, and empowering community participation to realize accountable and transparent village fund governance